Effects of N-acetyl cysteine on serum lipoprotein (a) and proteinuria in type 2 diabetic patients - Hamid Rouhi; Forouzan Ganji (Society of Diabetic Nephropathy Prevention, 2013)
Background: About 30-40% of diabetic patients who developed nephropathy have lipoprotein disorders, especially lipoprotein a [Lp(a)], which is related to atherosclerosis. Objectives: The aim of this study was to investigate the effect of N-acetyl cysteine (NAC) on the serum levels of Lp(a) and amount of proteinuria in a group of type 2 diabetic patients with diabetic nephropathy. Patients and Methods: A total of 40, type 2 diabetic (T2D) patients, patients with proteinuria, were randomly divided into two groups. The experimental group was treated by NAC (1200 mg/day) for two months in conjunction with conventional treatment for diabetes and hypertension. Control group received routine medications. Results: No significant change was identified in serum Lp(a) during treatment with NAC (P >0.05). However, NAC decreased the amount of proteinuria, serum triglyceride (TG) level and systolic blood pressure in experimental group compared to the control group (P <0.05). Conclusions: These findings suggest that treatment with NAC has no significant effect on the serum level of Lp (a). However, it has beneficial effects on the reduction of proteinuria, serum TG level and systolic blood pressure in T2D patients with nephropathy. Further prospective studies are needed to determine its full role.